PENGARUH TRANSAKSI ONLINE (E-COMMERCE), MODAL TERHADAP PENDAPATAN UMKM DI KECAMATAN BATANG KUIS - Dalimunthe, Hasbiana (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2025)
To develop a business, of course, income is needed that is equivalent to the capital that has been spent on the business. Therefore, to get the same income as the capital, you must pay attention to what can affect income, such as the transaction model and how much capital is spent. If you look at the data that has been studied, this data has reflected the existence of income that has fluctuated, but is inversely proportional to the increasing number of MSME business actors in the Batang Kuis area. This can be caused by several factors, one of which is the COVID-19 pandemic in 2022. This study aims to determine the effect of Online Transactions and capital on MSMEs in Batang Kuis District. This study uses a purposive sampling method which is calculated using the Slovin formula, namely 99.83 MSMEs rounded up to 100 MSMEs. There are 11 villages that are the population in this study, which use quantitative descriptive data types and use primary data sources taken using questionnaires and interviews. The results of this study indicate that online transactions), capital have a positive and significant effect on MSME income in Batang Kuis District.